Early detection of spinal cord compression: screening, clinical presentation, outcome and prognosis - Ali, Dalia Hasan; Alshafi, Abdullah Ibrahim; Aljehani, Eman Khalid; Alhilal, Jehad Ali; Balushi, Yasir Yar Al; Alkhuzaee, Ghazal Obaidallah; Alenezi, Mohammed Mamdouh; Aldallal, Khadija Mohamed; Alanazi, Marwan Mohammed; Saleem, Lama Mohammed (International Journal Of Community Medicine And Public Health, 2024)
Spinal cord compression (SCC) is a critical medical condition characterized by pressure on the spinal cord, which can lead to severe and potentially irreversible neurological damage if not promptly addressed. The causes of SCC are varied, including primary and metastatic tumors, traumatic injuries, degenerative diseases, and infections. Early detection of SCC is paramount for improving patient outcomes, minimizing risk of permanent deficits, and enhancing quality of life. This review examines etiology and clinical presentation of SCC, highlighting the significance of early screening and detection. Effective screening involves identifying high-risk individuals through risk stratification, utilizing advanced imaging techniques such as magnetic resonance imaging (MRI) and computed tomography (CT) scans, and maintaining clinical vigilance. Recognizing early symptoms, such as localized pain, neurological deficits, and autonomic dysfunction, is crucial for timely intervention. Prognosis of SCC improves significantly with early diagnosis and intervention. Treatment options include surgical decompression to relieve pressure, radiation therapy for tumor-related compression, and corticosteroids to reduce inflammation. Early intervention can prevent irreversible neurological damage and enhance recovery potential. Comprehensive rehabilitation, involving physical and occupational therapy, is critical for restoring function and improving quality of life.